A new variation of duplicated extrahepatic bile duct encountered intraoperatively on cholangiogram. Issue 10 (18th October 2022) - Armany, David; Allaway, Matthew; Gosal, Preet; Edirimanne, Senarath; Ahmed, Sulman
Abstract: A potentially devastating complication of laparoscopic cholecystectomy (LC) includes iatrogenic bile duct injury, the incidence of which has remained stable at 0.3% over the past three decades. Although there are several relative risks such as surgeon experience and patient factors (male sex, obesity, older age), misinterpretation of biliary tree anatomy contributes towards 80% of iatrogenic common bile duct (CBD) injuries. Although extremely rare, an isolated duplicated common hepatic duct anomaly with a normal CBD remains a potential variation to encounter during biliary surgery. With only one similar variation published worldwide, we report the second case encountered during LC and confirmed on cholangiogram. Given these anomalies are asymptomatic and perpetuate iatrogenic CBD injuries, awareness of this variation is crucial. Preoperative diagnosis is possible with the use of magnetic resonance cholangiopancreatography; however, such imaging is not routinely used prior to LC in Australia due to factors including expense and availability.